We are 'nature' defending itself entangling art, activism and autonomous zones - Frémeaux, Isabelle; Jordan, Jay (Vagabonds, 2021)
"In 2008, as the storms of the financial crash blew, Isabelle Fremeaux and Jay Jordan deserted the metropolis and their academic jobs, traveling across Europe in search of post-capitalist utopias. They wanted their art activism to no longer be uprooted. They arrived at a place French politicians had declared lost to the republic, otherwise know as the zad (the zone to defend): a messy but extraordinary canvas of commoning, illegally occupying 4,000 acres of wetlands where an international airport was planned. In 2018, the 40-year-long struggle snatched an incredible victory, defeating the airport expansion project through a powerful cocktail that merged creation and resistance. Fremeaux and Jordan blend rich eyewitness accounts with theory, inspired by a diverse array of approaches, from neo-animism to revolutionary biology, insurrectionary writings and radical art history"--